2014
DOI: 10.1111/tpj.12584
|View full text |Cite
|
Sign up to set email alerts
|

Small kernel 1 encodes a pentatricopeptide repeat protein required for mitochondrial nad7 transcript editing and seed development in maize (Zea mays) and rice (Oryza sativa)

Abstract: SUMMARYRNA editing modifies cytidines (C) to uridines (U) at specific sites in the transcripts of mitochondria and plastids, altering the amino acid specified by the DNA sequence. Here we report the identification of a critical editing factor of mitochondrial nad7 transcript via molecular characterization of a small kernel 1 (smk1) mutant in Zea mays (maize). Mutations in Smk1 arrest both the embryo and endosperm development. Cloning of Smk1 indicates that it encodes an E-subclass pentatricopeptide repeat (PPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
159
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(161 citation statements)
references
References 89 publications
(139 reference statements)
2
159
0
Order By: Relevance
“…This functional divergence is likely common to PPR ortholog pairs between monocot maize and dicot Arabidopsis, such as PPR2263 and MEF29 (Sosso et al ., ). However, between maize and rice, the function of the PPR othologs is highly conserved in editing mitochondrial transcripts (Liu et al ., ; Li et al ., ). The driving pressure behind these changes may be due to the coevolution of PPR proteins and organelle genomes during plant speciation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This functional divergence is likely common to PPR ortholog pairs between monocot maize and dicot Arabidopsis, such as PPR2263 and MEF29 (Sosso et al ., ). However, between maize and rice, the function of the PPR othologs is highly conserved in editing mitochondrial transcripts (Liu et al ., ; Li et al ., ). The driving pressure behind these changes may be due to the coevolution of PPR proteins and organelle genomes during plant speciation.…”
Section: Discussionmentioning
confidence: 97%
“…a–c). Likely, SMK1 is required for nad7‐ 836 editing and complex I assembly (Li et al ., ). Jointly, these data indicate that the accurate editing of nad7 is essential for its function in mitochondrial oxidative phosphorylation (Pineau et al ., ; Zhu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, many genes controlling maize kernel development have been cloned using kernel mutants identified from Robertson's Mutator stocks, including emp2 (empty pericarp2), emp4, emp5, emp16, dek1 (defective kernel1), dek35, maize pentatricopeptide repeat6, small kernel1, embryo defective14, U6 biogenesis-like1, and many others (Fu et al, 2002;Lid et al, 2002;Gutiérrez-Marcos et al, 2007;Manavski et al, 2012;Liu et al, 2013;Li et al, 2014Li et al, , 2015Chen et al, 2016;Xiu et al, 2016). Mutations in these genes usually have severe phenotypes in kernels, such as empty pericarp, where both embryo and endosperm cannot develop properly.…”
mentioning
confidence: 99%
“…However, none of the identified QTLs have been molecularly cloned or functionally characterized. In contrast, recent mutational studies have identified a number of genes that regulate kernel development, such as SMALL KERNEL 1 (encoding a PPR‐E protein; Li et al ., ), Supernumerary Aleurone Layers 1 (encoding a vacuolar sorting protein; Shen et al ., ), U6 Biogenesis‐Like 1 (encoding an RNA exonuclease; Li et al ., ) and Unhealthy Ribosome Biogenesis 2 (encoding an Urb2 domain‐containing protein; Wang et al ., ). Of particular interest, numerous studies have shown that maize mutants defective in auxin biosynthesis, transport or response display a wide range of abnormalities in the development of the embryo , endosperm, spikelet‐pair meristem or branch meristem, kernel number and kernel weight (Barazesh and McSteen, ; Bernardi et al ., ; Chen et al ., ; Forestan et al ., , ; Galli et al ., ; Scanlon et al ., ).…”
Section: Introductionmentioning
confidence: 99%